Pengaruh Promosi Penjualan Terhadap Keputusan Pembelian Sepeda Motor Honda Pada PT Cemara Agung Sejahtera - Nurdiana, Irwan; Aksan, Prihartono; Hamali, Arif Yusuf (STIE Ekuitas, 2019)
This research was conducted at PT Cemara Agung Sejahtera, aimed to know the correlation of sales promotion and purchasing decision, and also to analyze the influence of sales promotion to purchasing decision of Honda motorcyle at PT Cemara Agung Sejahtera. Respondents of this research are 71 selected using incidental sample technique. The method use is descriptive and associative, which tests the influence of dependent and independent variables using simple linear regression analysis. The result showed that sales promotion at PT Cemara Agung Sejahtera is in the category of good and purchasing decision is in the category of good. Result of the research showed that there is the influence of sales promotion to purchasing decision of Honda motorcyle at PT Cemara Agung Sejahtera and based on the interpretation of Pearson Product Moment correlation, this relationship is in the criteria of strong enough. The result showed that the hypothesis is proved: there is the influence of sales promotion to purchasing decision of Honda motorcyle at PT Cemara Agung Sejahtera significantly. Keywords: Sales Promotion; Purchasing Decision.